Red Yeast Rice Protects Hepatocytes conditions of Rats Receiving High Fat Diet - Wahyuningsih, Doti; Elyani, Helmin; Damayanti, Dini Sri; Yahya, Arif; Fadli, Muhammad Zainal (Journal of Tropical Life Science, 2019)
Triglyceride (TG) is a simple and the main lipid of the daily diet. Nowadays, TG is emerging as an independent risk factor for cardiovascular disease, and increasing clinical data that indicate a high level of this simple lipid in serum may alert and play a role in liver impairment. Red yeast rice (RYR) reduces serum TG in human and animals. The rice is widely used as a natural inhibitor of HMG-CoA reductase to correct serum cholesterol level. Bioactive components of the rice are well known to have antioxidant properties. This study examined whether RYR protects hepatocytes by evaluating the serum AST-ALT, HDL-Cholesterol (HDL-C), TG levels, and the number of liver foam cells in hypertriglyceridemic rats. Twenty male Wistar rats were grouped into 5. Four groups received a high-fat diet (HFD), 40 g/animal/day for 60 days to induce hypertriglyceridemic condition. Along with the HFD treatment, three groups received 108, 54, and 27 mg/kgBW/day of RYR, respectively. Two other groups received standard and only HFD diet, respectively. Intracardiac blood was collected for measuring AST and ALT using AST or ALT activity assay Kit, respectively, serum TG and HDL-C by Enzymatic Caloric Test. Hematoxylin-Eosin–stained 4µmm thick slices of liver tissues were prepared to count foam cell number by a light microscope with 400x magnificence. Data were analyzed using the Kruskal Wallis continued by the Mann Whitney U test. The p values of < 0.05 were considered to be significant. The present study found that 108, 54, and 27 mg/kgBW/day of RYR significantly decreased serum TG, HDL-C, AST, and ALT compared with those of hypertriglyceridemic rats receiving no RYR. The decreasing levels of the parameters were in relation to the doses of RYR. The doses of 108 and 54 mg/kgBW/day resulted in complete recovery of the liver tissues suffered from steatosis (p < 0.05). The RYR dose of 108 mg/KgBW/day completely corrects the serum HDL-C level. In conclusion, red yeast rice may have a potency to protect hepatocytes injuries due to hypertriglyceridemia.